The european-specific mitochondrial cluster J/T could confer an increased risk of insulin-resistance and type 2 diabetes : an analysis of the m.4216T > C and m.4917A > G variants - Crispim, Daisy (2011)
The aims of this studywere to investigate the contributions of the mitochondrialDNAm.4216T>Cand m.4917A> Gvariants, and also of the European-specific mitochondrial cluster J/T, to the development of type 2 diabetes mellitus in Caucasian-Brazilian patients from Southern Brazil. We analyzed 347 type 2 diabetes patients and 350 control subjects. Variant frequencies in patients and control subjects were compared using χ2 tests or odds ratio. We also compared clinical and laboratory characteristics among patients with and without the variants. We found that the frequencies of the m.4216T > C and m.4917A > G variants are higher in diabetic patients than in control subjects. Moreover, haplogroups J (partially defined by the presence of the m.4216T > C variant only) and T (partially defined by the presence of both m.4216T > C and m.4917A > G variants) are more frequent in the type 2 diabetic group than in the control group. Patients belonging to the cluster J/T are more insulin resistant than patients of other haplogroups. In conclusion, our results indicate the association of the cluster J/T (as suggested by analyses of the m.4216T > C and m.4917A > G variants) with insulin resistance and type 2 diabetes.